2013
DOI: 10.1186/1472-6920-13-83
|View full text |Cite
|
Sign up to set email alerts
|

Patient and preceptor attitudes towards teaching medical students in General Practice

Abstract: BackgroundCurricula in most western medical universities include teaching in the primary care setting as core elements. This affects GP-teachers, their patients and their interaction. Therefore, it was the aim of this study to assess the influence of the presence of medical students in the teaching practice on the attitudes of both GPs and patients.MethodsSeventy-four GP-preceptors were invited to answer an online survey. Patients attending consultations with a medical student present completed questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
1
25
0
2
Order By: Relevance
“…4,11 Overwhelmingly, physicians at KUSM-S valued having medical students on their service. Physicians felt energized by the presence of medical students, noted an overall increase in job satisfaction, enjoyed passing on their knowledge and being part of the education of the next generation of physicians, and felt valued by both students and the RMC administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,11 Overwhelmingly, physicians at KUSM-S valued having medical students on their service. Physicians felt energized by the presence of medical students, noted an overall increase in job satisfaction, enjoyed passing on their knowledge and being part of the education of the next generation of physicians, and felt valued by both students and the RMC administration.…”
Section: Discussionmentioning
confidence: 99%
“…based on physician comments she and other students heard during clerkships and on issues raised by other authors studying this issue. [4][5][6][7]11 The fourteen Likert scale questions are listed in A preliminary email was sent to the physicians explaining the nature of the questionnaire and when it would be delivered. Several days later, the physicians were notified that the survey was open.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies had a mixed target population of students, FPs and/or patients. [28][29][30] Thirteen studies were non-randomised controlled studies and 12 were pre-post (uncontrolled) studies (table 3). The sample size ranged from 16 to 1095 students, 3 to 146 teaching FPs and 94 to 2550 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…91 In some studies, a small number of patients (1-6%) reported a negative effect of the student's presence during the consultation, such as longer consultations 31 86 91 or more difficulty/less space to talk about personal problems. 87 91 Although one study reported a significant difference in length of consultations with and without students present as recorded by the FPs, 88 in other studies, the majority of patients did not think that either their consultation took longer when a student was present 29 or that time with their FP or the FP's attention was reduced due to the presence of a student. 31 …”
mentioning
confidence: 97%
“…From a patient perspective, research to date suggests that although in general patients are supportive of a medical student being present during their consultation, there is a proportion of patients (albeit small) who have concerns about this . Additionally, many patients believe they play an important role in the learning experience of medical students .…”
Section: Introductionmentioning
confidence: 99%